2012
DOI: 10.1007/s00246-012-0516-0
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Unexplained Cardiac Arrest in Apparently Healthy Children: A Single-Center Experience

Abstract: Objective To determine the causes of sudden cardiac arrest (SCA) in apparently healthy children in a single center in the era of primary prevention (screening questionnaire, SQ) and secondary prevention (automated external defibrillator, AED and automated implantable cardioverter defibrillator, AICD). Study Design Any child (0–18 year’s age) without prior known disease except for attention deficit disorder who underwent out-of-the hospital cardiopulmonary resuscitation was included in the study as SCA. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The addition of a screening ECG to the history and physical examination increases the detection of cardiac disorders potentially at risk of SCA/D in athletes 39–41 54 68 70 72 83. An estimated 60% of the disorders associated with SCA/D in young individuals may have detectable ECG abnormalities 17.…”
Section: Ecg For the Cardiovascular Screening Of Athletesmentioning
confidence: 99%
“…The addition of a screening ECG to the history and physical examination increases the detection of cardiac disorders potentially at risk of SCA/D in athletes 39–41 54 68 70 72 83. An estimated 60% of the disorders associated with SCA/D in young individuals may have detectable ECG abnormalities 17.…”
Section: Ecg For the Cardiovascular Screening Of Athletesmentioning
confidence: 99%
“…Sudden deaths such as this, although uncommon, do occur in this population, regardless of vaccination history. [36][37][38] VAERS monitors the safety of all vaccinations, including 4vHPV. 39 From June 2006 to March 2013, 96 reports of death after receipt of 4vHPV vaccine were submitted to VAERS.…”
Section: Discussionmentioning
confidence: 99%
“…21) In one single center study, the etiology for sudden cardiac arrest was identified in 57% of the cases, mostly in those above 1 year of age and among these the majority of had a cardiac etiology (50%) while 7% had rupture of an arteriovenous malformation. 12) Acute myocarditis is a disease with a variable natural history and is difficult to diagnose. Often, the symptoms of acute myocarditis are initially flu like, either of the upper respiratory or gastrointestinal tract, before any cardiac symptoms appear.…”
Section: Discussionmentioning
confidence: 99%
“… 11) Cardiac causes were most common, but an etiology was less evident in infants in comparison to older children. 12) Although the definite causes have not been identified, vasovagal reaction has been suggested as a cause of cardiac arrest following venipuncture, resulting in serious cardiac dysfunction, such as asystole.…”
Section: Introductionmentioning
confidence: 99%